Tinjauan Pustaka : Promosi Kesehatan dan Gizi Pada Populasi Migran: Literature Review: Health and Nutrition Promotion in Migrant Populations - Ira Yunianti; Setianingrum, Wulan; Fitriana, Destia Ika; Puspikawati, Septa Indra (Calvaria Medical Journal, 2026)
Background: Migrants are a vulnerable group experiencing various health and nutritional problems due to environmental changes, limited access to health services, cultural barriers, and acculturation stress. Therefore, health and nutrition promotion are important strategies to improve the quality of life and well-being of migrant populations. Objectives: To identify the forms of health and nutrition promotion interventions in migrant populations, assess their effectiveness, and explore barriers to their implementation. Methods: This study used a Systematic Literature Review method based on the PRISMA 2020 guidelines. Article searches were conducted through the Google Scholar database using the keywords "migration" AND "health promotion" AND "nutrition". Articles published in 2019–2024 were selected based on predetermined inclusion and exclusion criteria. A total of 6 articles met the criteria and were analyzed narratively. Results: The review showed that community-based and participatory interventions, such as CBPR and salutogenic programs, were effective in improving quality of life, strengthening social support, and reducing stress levels in migrants. In addition, health-promotive behaviors and self-efficacy were shown to contribute positively to the quality of life of migrant workers, while acculturation stress had a negative effect. In terms of nutrition, the main barriers identified include language barriers, economic constraints, low health literacy, a lack of culturally appropriate educational materials, and concerns about immigration policies that hinder access to nutrition assistance programs. Conclusion: The success of health and nutrition promotion among migrant populations is influenced by individual, social, cultural, and structural factors. A culturally sensitive, community-based approach, supported by strengthening self-efficacy, social support, and increasing access to health information, has the potential to provide more effective and sustainable benefits for migrant populations.